The Impact of Priming Power on Sexual Harassment Proclivity in Male Correctional Officers - (:unkn) unknown (My University, 2017)
Previous research has shown that holding a position of power has a significant impact on the likelihood of an individual engaging in sexual harassment. Additionally, cultural scripts among men encourage seeking power, and exerting their power upon others through acts such as sexual harassment. Correctional officers exist in an environment that necessitates the adherence and utilization of power to control dangerous environments. The combination of traditional male norms and the need to access power and authority for male correctional officers could lead to an increase in sexual harassment proclivity. This study will explore whether a short term priming of power can increase sexual harassment proclivity within a sample of male correctional officers. Additionally, it will be tested whether adherence to male norms impacts sexual harassment proclivity, and whether maturation through a correctional officer position influences proclivity as well. Significant difficulties occurred in the data collection process. The findings, the challenges in data collection, and means of avoiding them in future research with correctional officers are discussed.
Keywords: Correctional Officers; Male Norms; Power; Sexual Harassment